Escaping the typical English classroom in Iceland : customizing an escape room to support communicative language teaching and curricular goals through game-based learning - Maureen Sarah McLaughlin 1980- (2023)
English is encountered in a variety of ways by Icelandic elementary school pupils, often daily, either through watching TV, listening to music, playing video games, through internet platforms such as TikTok/YouTube, and in classrooms. However, research into English language learning in Iceland has shown that much of this input is receptive and does not provide sufficient opportunities to enhance productive skills, i.e. using English for self-expression. One of the primary objectives set by the Icelandic national curriculum (2013) for foreign language education is that students can express themselves authentically in the target language. Prior research has shown that more can be done to enhance the use of productive skills in the language classroom. One approach that can influence authentic language use is to implement more collaborative and task-based activities, including games. To investigate the viability of such an activity, an action research project was designed and conducted to focus on the potential of using a classroom escape room to attain curriculum goals and support communicative competence. The puzzles and teaching materials created for the intervention were related to topics covered in the English lessons throughout the year. Participants included the researcher/student teacher, the teacher and 18 pupils from a fifth grade Icelandic elementary school. Data was collected through a post-intervention interview, observations from the researcher, and through surveys completed by the pupils. Results were positive, with teachers and students reporting high satisfaction and a number of perceived benefits regarding the classroom escape room as a language learning resource. Results also indicated two areas that need to be reassessed in order to make it a more effective resource for supporting communicative competence. Once efforts are made to rectify these issues, the classroom escape room has high potential as an effective tool for supporting the communicative competences and skills of the pupils. The ...